STRATEGI PENGEMBANGAN USAHA WANITA NELAYAN DALAM MENGOLAH HASIL PERIKANAN BERBASIS KELOMPOK - Ratna Diyah Palupi; Ira Ira; Asriyana Asriyana (Jurnal Bisnis Perikanan (Journal of Fishery Business), 2016)
This study aimed are to analyze the financial feasibility and development strategic of the fish balls business in the Bubu Village. The research activities conducted July-September 2016 at Bubu Village Kambowa District of North Buton in Southeast Sulawesi. Data collected by observation, interviews and literature. The results showed that the business of fish balls in Bubu Village has a good business prospective and should be developed viewed from various aspects, namely marketing, financial aspects as well as the direction of enterprise development. Supporting factors the business of fish balls, namely a lack of competition, infrastructure and facilities are within easy reach, as well as the marketing of the product is very good because it is supported by the strategic position of the village. Factors that inhibit weakness are the availability of raw materials, including seasonal and can be updated by means of taking raw materials from other regions. Financial aspect is eligible to run for a short-term (current conditions) and long term (10 years). Keywords: Business, Fish balls, Bubu Village, Development Strategic